Tocilizumab for severe COVID-19 related illness – A community academic medical center experience (2020)
The SARS-CoV-2 virus responsible for the COVID-19 pandemic can result in severe or fatal disease in a subset of infected patients. While the pathogenesis of severe COVID-19 disease has yet to be fully elucidated, an overexuberant and harmful immune response to the SARS-CoV-2 virus may be a pivotal aspect of critical illness in this patient population. The inflammatory cytokine, IL-6, has been found to be consistently elevated in severely ill COVID-19 patients, prompting speculation that IL-6 is an important driver of the pathologic process. The inappropriately elevated levels of inflammatory cytokines in COVID-19 patients is similar to cytokine release syndrome (CRS) observed in cell therapy patients. We sought to describe outcomes in a series of severely ill patients with COVID-19 CRS following treatment with anti-IL-6/IL-6-Receptor (anti-IL-6/IL-6-R) therapy, including tocilizumab or siltuximab. At our academic community medical center, we formed a multi-disciplinary committee for selecting severely ill COVID-19 patients for therapy with anti-IL-6 or IL-6-R agents. Key selection criteria included evidence of hyperinflammation, most notably elevated levels of C-reactive protein (CRP) and ferritin, and an increasing oxygen requirement. By the data cutoff point, we treated 31 patients with anti-IL-6/IL6-R agents including 12 who had already been intubated. Overall, 27 (87%) patients are alive and 24 (77%) have been discharged from the hospital. Clinical responses to anti-IL-6/IL-6-R therapy were accompanied by significant decreases in temperature, oxygen requirement, CRP, IL-6, and IL-10 levels. Based on these data, we believe anti-IL-6/IL-6-R therapy can be effective in managing early CRS related to COVID-19 disease. Further study of anti-IL-6/IL-6-R therapy alone and in combination with other classes of therapeutics is warranted and trials are underway.